PENGEMBANGAN KETERAMPILAN SISWA DI BIDANG DESAIN GRAFIS DAN E-COMMERCE DI BIDANG JASA DIGITAL PRINTING - Dony Novaliendry (Jurnal Teknologi Informasi dan Pendidikan, 2019)
Education plays an important role in producing people who can make changes by producing ideas in learning. However, the current problem is the readiness of graduates from schools to be able to continue their survival in finding work. One of them is the lack of skills possessed by graduates of high school/vocational school at this time and also very high competitiveness in getting a job. At present the workforce with graphic and multimedia design skills has considerable opportunities in industries engaged in digital printing printing services. The solution offered is to improve the skills of high school/vocational graduates through digital printing training and marketing their products online.